2012
DOI: 10.1051/alr/2012031
|View full text |Cite
|
Sign up to set email alerts
|

Schooling behavior of juvenile yellowfin tunaThunnus albacaresaround a fish aggregating device (FAD) in the Philippines

Abstract: -A fish aggregating device (FAD) called a payao is conventionally installed to catch pelagic species in the Philippines. The waters around the Philippines are important regions for yellowfin tuna stocks because they include spawning grounds and nurseries. To understand the schooling behavior of juvenile yellowfin tuna Thunnus albacares around a payao, 13 juveniles (20.5−24.0 cm fork length) double tagged with ultrasonic transmitters (V7-2L-R256; Vemco Ltd.) and data loggers (DST-micro; Star-Oddi Ltd.) were rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…Mitsunaga et al . () investigated the behavior of yellowfin tuna around an anchored FAD at the Philippines and reported that detection rates were higher during the day than during the night for most individuals, which is consistent with our observations. Klimley and Holloway () also reported that yellowfin tuna in Hawaii primarily visited anchored FADs during the day.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Mitsunaga et al . () investigated the behavior of yellowfin tuna around an anchored FAD at the Philippines and reported that detection rates were higher during the day than during the night for most individuals, which is consistent with our observations. Klimley and Holloway () also reported that yellowfin tuna in Hawaii primarily visited anchored FADs during the day.…”
Section: Discussionsupporting
confidence: 89%
“…There is potential for the selective harvest of tuna species if their swimming depth differs around FADs. A number of studies have evaluated the vertical behavior of the aforementioned tuna species (the so‐called ‘tropical tunas’) associated with floating objects, including FADs (Cayré and Chabanne, ; Holland et al ., ; Cayré, ; Marsac and Cayré, ; Klimley and Holloway, ; Dagorn et al ., ; Schaefer and Fuller, , , , ; Musyl et al ., ; Ohta and Kakuma, ; Leroy et al ., ; Schaefer et al ., ; Mitsunaga et al ., , ; Matsumoto et al ., ; Weng et al ., ). Most of these studies evaluated the behavior of tropical tunas around anchored FADs whereas few have evaluated behavior around drifting FADs because of the difficulty and expense of tracking FADs.…”
Section: Introductionmentioning
confidence: 99%
“…These tagged juvenile yellowfin tuna forage in a network of anchored FADs as they start to migrate outside the locations of these fishing grounds. Moreover, a follow-up study by the same authors also showed that a tagged juvenile yellowfin tuna was caught 12 km away from the original tagging site which means that juvenile yellowfin tunas can easily move from one FAD to the other (Mitsunaga et al, 2013). In contrast, investigations of adult yellowfin tunas by Ohta and Kakuma (2005) showed that the fish stayed for a maximum of 55 days around a single FAD while Dagorn et al (2006) reported that they stayed for a maximum of 151 days on a network of FADs.…”
Section: Semi-structured Interviewmentioning
confidence: 99%
“…Keberadaan rumpon di suatu perairan dapat mempengaruhi tingkah laku dan pola pergerakan yuwana madidihang dan mata besar (Leroy et al 2013;Mitsunaga et al 2013;Weng et al 2013;Mitsunaga et al 2012). Penelitian Mitsunaga et al (2013) memperlihatkan bahwa pada siang hari yuwana tuna dengan panjang cagak 20,5-24 cm terkonsentrasi di dekat rumpon pada kedalaman sekitar 20-30 meter, sedangkan malam hari terdistribusi di sekitar rumpon pada kedalaman sekitar 11-20 meter.…”
Section: Proporsi Yuwanaunclassified